Effect of different contents of WO3 and B2O3 on the structure and thermal, mechanical, corrosion properties of phosphate glass. (1st May 2023) - Shi, Xiao-zhao; Zhu, Mengting; Liu, Lei; Liu, Tao-yong; Bai, Long-teng; Yang, Xiao-hui; Cao, Pei; Gu, Yi
Abstract: In this experiment, 20P2 O5 –50SnF2 -(30-x-y)SnO-xWO3 -yB2 O3 (x = 0, y = 0, 5, 10, 15; x = 5, 10, 15, y = 0; x = 10, 5, y = 5, 10mol%) phosphate glasses were prepared. In this paper, the effect of the addition of WO3 and B2 O3 on the properties of phosphate glasses was investigated. The results show that the network structure of all glass samples is basically composed of Q1 and Q0 short chain groups. The addition of WO3 disrupts the network structure of the glass and leads to a decrease in the glass thermal, mechanical, corrosion properties. B2 O3 participates in the formation of the glass as a [BO4 ] structural unit, which strengthens the network structure and thus improves the glass properties. However, with the increase of B2 O3, some of the B2 O3 existed as [BO3 ], which reduced the cross-linkage of the glass structure and the glass properties appeared abnormal. In the glass with the coexistence of WO3 and B2 O3, the glass properties were better, especially the chemical stability of the glass was significantly improved. The smallest weight loss rate in the aqueous solution is only 9.52 × 10 −7  g·cm −2 ·min −1 .